Branding Universities using Social Media: how brand value is created (case of Kazakhstan) - Nurman, D. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2020)
n a competitive education market, universities pay special attention to brand image in order to ensure high demand among their target audience. The positive image of each university affects the prestige of an individual educational institution, as well as the formation of an overall positive image and rating of the state education system. In this regard, the relevance of studying the brand image of higher educational institutions arises. The issues of the need to form and maintain the brand of educational institutions of higher professional education, the functions and elements of the brand structure are considered. The article reflects the specifics of educational services in the context of the formation of the brand of the university. A review of approaches to determining the criteria for evaluating university brands according to various independent ratings is carried out. The study analyzes the factor variables that affect the reputation and relevance of the university among students. In addition to the theoretical part of the study, the article examines the results of interviews with respondents.
Keywords: Brand image of higher education institutions, marketing communications, Influence marketing